The relationship between unimanual capacity and bimanual performance in children with congenital hemiplegia - Sakzewski, L.; Ziviani, J.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2010)
Aim: This study explores the relationship between unimanual capacity and bimanual performance for children with congenital hemiplegia aged 5 to 16 years. It also examines the relationship between impairments and unimanual capacity and bimanual performance. Method: Participants in this cross-sectional study attended a screening assessment before participating in a large, randomized trial. They comprised 70 children with congenital hemiplegia (39 males, 31 females; mean age 10y 6mo, SD 3y); 18 were classified in the Manual Ability Classification System level I, 51 in level II, and one in level III. Eighteen were in Gross Motor Function Classification System, level I and 52 in level II. Sixty-five participants had spasticity and five had dystonia and spasticity. Fifteen typically developing children (7 males, 8 females; mean age 8y 8mo, SD 2y 7mo), matched to study participants for age and sex, were recruited as a comparison group for measures of sensation, grip strength, and movement efficiency. Outcome measures for unimanual capacity were the Melbourne Assessment of Unilateral Upper Limb Function (MUUL), and the Jebsen-Taylor Hand Function Test (JTHFT). The Assisting Hand Assessment (AHA) evaluated bimanual performance. Upper limb impairments were measured using assessments of stereognosis, moving two-point discrimination, spasticity, and grip strength. Results: There was a strong relationship between unimanual capacity (MUUL) and bimanual performance (AHA; r=0.83). Linear regression indicated MUUL and stereognosis accounted for 75% of the variance in AHA logit scores. Sensory measures were moderately correlated with unimanual capacity and bimanual performance. Age, sex, and grip strength did not significantly influence bimanual performance. There was no difference between children with right- and left-sided hemiplegia for motor performance. Interpretation: Findings of our study confirm a strong relationship between unimanual capacity and bimanual performance in a cohort of children with congenital hemiplegia. However, the directionality of the relationship is unknown and therapists cannot assume improvements in unimanual capacity will lead to gains in bimanual performance. © The Authors. Journal compilation © Mac Keith Press 2010.